2021
DOI: 10.1126/sciadv.abd1204
|View full text |Cite
|
Sign up to set email alerts
|

How Jupiter’s unusual magnetospheric topology structures its aurora

Abstract: Jupiter’s bright persistent polar aurora and Earth’s dark polar region indicate that the planets’ magnetospheric topologies are very different. High-resolution global simulations show that the reconnection rate at the interface between the interplanetary and jovian magnetic fields is too slow to generate a magnetically open, Earth-like polar cap on the time scale of planetary rotation, resulting in only a small crescent-shaped region of magnetic flux interconnected with the interplanetary magnetic field. Most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 65 publications
0
61
0
Order By: Relevance
“…Recently, Zhang et al. (2021) have also shown that the longitudinal width of footprint of blue field lines in Figure 1 is very narrow. It seems reasonable to draw only one Dungey cell in contact with the main oval, as in Cowley, Bunce, Stallard and Miller (2003).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Recently, Zhang et al. (2021) have also shown that the longitudinal width of footprint of blue field lines in Figure 1 is very narrow. It seems reasonable to draw only one Dungey cell in contact with the main oval, as in Cowley, Bunce, Stallard and Miller (2003).…”
Section: Resultsmentioning
confidence: 87%
“…On the other hand, a different result is presented by Zhang et al (2021), showing downward FAC on closed field lines. In the present paper, all magenta field lines extend far into the lobe, but in Zhang et al (2021), many polar cap field lines connect to the opposite hemisphere passing through the evening frank. It is quite apparent that this difference is extremely serious.…”
Section: Interaction Between the Solar Wind And Rotating Magnetic Fieldmentioning
confidence: 89%
“…Polar auroral flares can be extremely dynamic, with their intensity increasing by orders of magnitude within 10 s (Waite et al, 2001). Recently, Zhang et al (2021) reveal that the magnetic field lines connecting the polar regions are helical and closed between the northern and southern ionospheres.…”
mentioning
confidence: 99%
“…Although reported in similar region within the polar aurora as the features discussed here, the difference in morphology, typical brightness, feature growth as well as periodic behavior suggest a different origin. They found these repetitive spots to corotate with Jupiter, ruling out their potential noon‐facing magnetospheric cusp‐related origin, although the non‐trivial magnetic field topology in that region might complicate the picture (Zhang et al., 2020).…”
Section: Discussionmentioning
confidence: 99%